Embodied Impacts in Buildings: A Systematic Review of Life Cycle Gaps and Sectoral Integration Strategies - Tsvetelina Spasova Bacheva; Javier F. Raposo Grau (Buildings)
The growing focus on operational energy efficiency in the building sector has revealed a critical gap in addressing embodied impacts—carbon emissions and energy demands associated with the production, construction, use, and end-of-life stages of buildings. This research addresses this gap by introducing an integrated framework encouraging collaboration across academia, industry, and policymakers. Based on a systematic analysis of current research, the study identifies trends and provides actionable recommendations to enhance embodied impacts assessments. The findings reveal limited representation in key areas like Building Information Modeling (BIM) and policy frameworks, alongside a strong geographical imbalance in research, with 60% of the investigations originating from only five countries. Life cycle stages beyond “cradle-to-gate” remain marginally explored, with only 39% concerning end-of-life or reuse phases. Moreover, 65% of stakeholder engagement is confined to LCA specialists and building designers, highlighting the need for broader participation. This study proposes a comprehensive framework promoting a holistic approach to embodied impacts, advocating their integration into academic curricula and urging industry professionals to adopt collaborative and sustainable practices. By clarifying sectoral gaps and outlining targeted pathways for integration, this study provides a foundation for translating embodied impact research into practical application and regulatory frameworks.